HUBUNGAN STATUS GIZI, STATUS SOSIAL EKONOMI, DAN TINGKAT PENDIDIKAN DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI PUSKESMAS PAMPANG, KOTA MAKASSAR, TAHUN 2021–2022 - Nur Aisyah; Andi Alifia Ayu Delima; Darmawansyih; Dewi Setiawati; Zulfahmi Alwi (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2026)
Introduction: Anemia in pregnancy is a condition in which pregnant women have hemoglobin (Hb) levels of <11 g/dL in the first and third trimesters, and <10.5 g/dL in the second trimester. Anemia during pregnancy can increase the risk of impaired fetal growth, higher perinatal mortality, preterm delivery, low birth weight, and decreased immunity in both mothers and infants. Objective: This study aimed to determine the relationship between nutritional status, socioeconomic status, and educational level and the incidence of anemia among pregnant women. Methods: This study employed a quantitative observational design with a cross-sectional approach and purposive sampling technique. A total of 173 pregnant women were selected from a population of 306. Secondary data were obtained from medical records. Results: The results showed a significant relationship between socioeconomic status and the incidence of anemia (p = 0.000). However, no significant relationship was found between nutritional status and the incidence of anemia (p = 0.193), nor between educational level and the incidence of anemia (p = 0.960). Conclusion: Socioeconomic status was significantly associated with anemia among pregnant women, while nutritional status and educational level were not.